Como o humano se põe O enterro de Fichte no fragmento hölderliniano de Píndaro Os Asilos (Revista Eletrônica Estudos Hegelianos, 2021)
The aim of the present essay is to assign a certain consistency to Hölderlin’s Pindar-fragment Die Asyle, by summarizing it and also explaining how one may understand what I call Fichte’s Beisetzung